Migrant Networks and Foreign Direct Investment - Javorcik, Beata S. (World Bank, Washington, DC, 2012)
While there exists sizeable literature documenting the importance of ethnic networks for international trade, little attention has been devoted to studying the effects of networks on foreign direct investment (FDI). The existence of ethnic networks may positively affect FDI by promoting information flows across international borders and by serving as a contract enforcement mechanism. This paper investigates the link between the presence of migrants in the United States and U.S. FDI in the migrants' countries of origin, taking into account the potential endogeneity concerns. The results suggest that U.S. FDI abroad is positively correlated with the presence of migrants from the host country. The data further indicate that the relationship between FDI and migration is driven by the presence of migrants with a college education.